2022
DOI: 10.1101/2022.10.04.510611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arterial cells support the development of human hematopoietic progenitors in vitro via secretion of IGFBP2

Abstract: Hematopoietic stem and progenitor cells develop from the hemogenic endothelium located in various sites during development, including the dorsal aorta from where Hematopoietic Stem Cells (HSCs) emerge. This process has proven especially challenging to recapitulate in vitro from pluripotent stem cells and further studies are needed to pinpoint the missing stimuli in vitro. Here, we compared iPSC-derived endothelial cells and in vivo HSC-primed hemogenic endothelium and identified 9 transcription factors express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We identified 4 genes that encoded secreted factors in this category, ANGPTL7 , ABI3BP , FDCSP , and IGFBP6 . IGFBP6 was particularly interesting due to the emerging literature about the role of the IGFBP family member IGFBP2 in haematopoiesis and erythropoiesis ( Petazzi et al, 2022 ), and therefore IGFBP6 expression was confirmed via qRT-PCR and was significantly upregulated in 4OH-tamoxifen treated iKLF1-WT but not iKLF1-E325K (iCDA4.1 and iCDA4.20) iPSC-DMs ( Figure 5A ). IGFBP6 was added in combination with NRG1, NOV, CCL13 and TNFSF10 to UCB-derived CD34 + cells under the erythroid cell differentiation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4 genes that encoded secreted factors in this category, ANGPTL7 , ABI3BP , FDCSP , and IGFBP6 . IGFBP6 was particularly interesting due to the emerging literature about the role of the IGFBP family member IGFBP2 in haematopoiesis and erythropoiesis ( Petazzi et al, 2022 ), and therefore IGFBP6 expression was confirmed via qRT-PCR and was significantly upregulated in 4OH-tamoxifen treated iKLF1-WT but not iKLF1-E325K (iCDA4.1 and iCDA4.20) iPSC-DMs ( Figure 5A ). IGFBP6 was added in combination with NRG1, NOV, CCL13 and TNFSF10 to UCB-derived CD34 + cells under the erythroid cell differentiation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of the protocol is that the endothelial cells derived We have previously shown that iPSC-derived endothelial cells mimic the heterogeneous arteriovenous cellular identities 27 similar to that observed in the fetal dorsal aorta 28 , 29 , 30 . This is of particular importance in the context of vessel development and cellular specification, known to be controlled by blood circulation.…”
Section: Seeding Cells Into the Fluidic Channelmentioning
confidence: 90%